Coal combustion products (CCPs) : characteristics, utilization and beneficiation - Robl, Thomas L.; Oberlink, Anne; Jones, Rod (Woodhead Publishing in energy., 2017)
This book provides a valuable resource for engineers and scientists from the coal, cement, concrete, and construction industries seeking an in-depth guide to the characteristics, utilization, beneficiation, and environmental impacts of coal combustion by-products.